A case of Falciparum malaria presenting with features of functional bowel obstruction - Albashir, Ahmed Abdalazim Dafallah (Oxf Med Case Reports, 2020)
Malaria is the most common tropical disease in Sudan, which is caused by an infection with Plasmodium protozoa transmitted by an infective female Anopheles mosquito. Headache, fever, cough, fatigue, malaise, shaking chills, arthralgia and myalgia are the cardinal features of malaria, but occasionally, it has an atypical presentation. Intestinal obstruction as a complication is an extremely rare presentation. Here within, we describe a 28-year-old Sudanese man who has presented with of colicky abdominal pain, absolute constipation for two days and fever. Blood film for malaria was positive for Plasmodium falciparum. Intravenous artesunate injections have resulted in the resolution of symptoms of bowel obstruction. In conclusion, malaria should be suspected in any febrile patient with the features of bowel obstruction especially in an endemic area or if the patient has recently travelled to an endemic area with malaria. Treatment of malaria will result in the resolution of symptoms of functional bowel obstruction.